2023
DOI: 10.1002/pro.4816
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of disulfide bond formation in TEM‐1 versus CTX‐M‐9 β‐lactamase

Miranda Villanueva,
Lauren E. Vostal,
Drew N. Cohen
et al.

Abstract: To investigate how disulfide bonds can impact protein energy landscapes, we surveyed the effects of adding or removing a disulfide in two β‐lactamase enzymes, TEM‐1 and CTX‐M‐9. The homologs share a structure and 38% sequence identity, but only TEM‐1 contains a native disulfide bond. They also differ in thermodynamic stability and in the number of states populated at equilibrium: CTX‐M‐9 is two‐state whereas TEM‐1 has an additional intermediate state. We hypothesized the disulfide bond is the major underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…In this case, however, the part that displaces is not the same as the one that gets displaced, as seen in regular domain swapping (Brangulis et al, 2024 ; Cahyona et al, 2020 ; Mascarenhas & Gosavi, 2017 ; Sakai et al, 2023 ). In a recent study, another β‐lactamase, CTX‐M‐9, was shown to form oligomers as the result of the introduction of two Cys residues, and domain swapping was proposed as a mechanism (Villanueva et al, 2024 ). It illustrates that small surface changes can enhance homomeric interactions.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, however, the part that displaces is not the same as the one that gets displaced, as seen in regular domain swapping (Brangulis et al, 2024 ; Cahyona et al, 2020 ; Mascarenhas & Gosavi, 2017 ; Sakai et al, 2023 ). In a recent study, another β‐lactamase, CTX‐M‐9, was shown to form oligomers as the result of the introduction of two Cys residues, and domain swapping was proposed as a mechanism (Villanueva et al, 2024 ). It illustrates that small surface changes can enhance homomeric interactions.…”
Section: Discussionmentioning
confidence: 99%